2016
DOI: 10.3389/fsurg.2016.00065
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lymph Node Burden on Survival of High-risk Prostate Cancer Patients Following Radical Prostatectomy and Pelvic Lymph Node Dissection

Abstract: AimTo determine the impact of the extent of lymph node invasion (LNI) on long-term oncological outcomes after radical prostatectomy (RP).Material and methodsIn this retrospective study, we examined the data of 1,249 high-risk, non-metastatic PCa patients treated with RP and pelvic lymph node dissection (PLND) between 1989 and 2011 at eight different tertiary institutions. We fitted univariate and multivariate Cox models to assess independent predictors of cancer-specific survival (CSS) and overall survival (OS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…A total of 141,222 patients (ranging from 51 to 65,633) underwent RP for PCa management, of which 31,421 patients were reported to have PSMs. Nine studies [ 8 , 17 , 19 , 20 , 30 , 32 , 34 , 36 , 37 , 42 ] reported the use of radiotherapy as an adjuvant therapy after RP, and the proportion of patients who received aRT was 0.2–69%. Of the 32 studies, 11 were conducted in North America, 10 in Asia, 8 in Europe and 3 at international multi-centres.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 141,222 patients (ranging from 51 to 65,633) underwent RP for PCa management, of which 31,421 patients were reported to have PSMs. Nine studies [ 8 , 17 , 19 , 20 , 30 , 32 , 34 , 36 , 37 , 42 ] reported the use of radiotherapy as an adjuvant therapy after RP, and the proportion of patients who received aRT was 0.2–69%. Of the 32 studies, 11 were conducted in North America, 10 in Asia, 8 in Europe and 3 at international multi-centres.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is increasing evidence that the number of metastatic nodes can stratify subpopulations with different prognosis. In high-risk PCA, it has been shown that the lymph node burden is an independent prognostic factor associated with both cancer-specific and overall survival [10,20]. So far, clinical factors predicting the loads of LNI are important for stratifying the high-risk PCA population who is subject to multimodality treatments.…”
Section: Discussionmentioning
confidence: 99%
“…A large multicenter retrospective study including an old cohort has shown that in high-risk selected patients with at least 10 nodes removed (median 15), the rate of LNI was 36.1%, which included ROC, receiverreceiver operating characteristic; AUC, area under the curve; pN, pathologic nodal staging status; pN0, absence of nodal metastases; pN1(u), prostate cancer with unilateral metastatic nodes; pN1(b), prostate cancer with bilateral nodal metastases; PSA, prostate-specific antigen; P(p), proportion of biopsy positive cores. 26.4% of cases having 1-3 positive nodes and 9.7% of patients with more than 3 positive lymph nodes [10]. In a dated North American cohort, a nomogram predicting pathological outcomes in high-risk patients has been proposed by evaluating a median LN(n) of 5 [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is recommended that pelvic lymph nodes (PLN) be included in the target volume for those patients. In addition, there is evidence of clinical benefit from PLN treatment in the high‐risk population . Given the low α/β ratio attributed to prostate cancer, (approximately 1.5–1.8), hypofractionation is potentially more beneficial for occult nodal metastases in high‐risk patients .…”
Section: Introductionmentioning
confidence: 99%